CGIAR Research Program on Climate Change, Agriculture and Food Security - Plan of Work and Budget 2019 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
A largely new portfolio of projects will be initiated in 2019 ("refresh"), to better fit the new end date of CRPs (2019-2021), and based on discussions of the Independent Steering Committee. Six regional or thematic meetings were held with project participants and external stakeholders to shape and discuss the portfolio. However, theories of change (ToC) largely remain unchanged from those in the CRP proposal. Where there were programmatic changes, they were largely related to partnerships (to better achieve outcomes), and greater emphasis placed on certain aspects of the original ToC. All Flagships have increased their focus on youth-related issues. There has been an increase in activity in Ethiopia by all Flagships, given the strategic decision to shift the regional coordination office to Addis Ababa, and consequently slightly reduced core supported activities in other countries in East Africa. On the other hand, there is a significant increase in bilateral-supported investment for research and scaled implementation of climate-smart agriculture (CSA) technologies and practices in Kenya, Uganda and Tanzania, with a focus on making value chains and private sector engagement climate-smart. Shifts in Flagships are discussed under 4.1.